2022
DOI: 10.3389/fendo.2022.1071465
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index is associated with diabetic kidney disease in Type 2 diabetes mellitus patients: Evidence from NHANES 2011-2018

Abstract: ObjectiveDiabetic kidney disease (DKD) is the most common chronic kidney disease (CKD) and has the highest prevalence of end-stage kidney disease (ESKD) globally, owing mostly to the rise in Type 2 diabetes mellitus (T2DM) correlated with obesity. Current research suggested that the immune response and inflammation may play a role in the pathophysiology of T2DM. The systemic immune-inflammation index (SII) is a novel and integrated inflammatory biomarker that has not yet been linked to DKD. We aimed to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 59 publications
(68 reference statements)
4
84
0
Order By: Relevance
“…Increased SII was associated with poor survival in ASCVD patients. Guo et al [ 32 ] found that SII levels in T2DM patients were associated with the development of diabetic kidney disease (DKD). SII may be a cost-effective and simple method to detect DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Increased SII was associated with poor survival in ASCVD patients. Guo et al [ 32 ] found that SII levels in T2DM patients were associated with the development of diabetic kidney disease (DKD). SII may be a cost-effective and simple method to detect DKD.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study found that ln-SII at baseline was associated with all causes of death from any cause in the United States ASCVD population in the NHANES group [22]. Increased SII in ASCVD individuals is related to poor survival [23].In addition, higher levels of SII are related to an increased risk of hepatic steatosis[8], peripheral arterial disease [9], isolated coronary artery ectasia [10], urinary albuminuria excretion [5], diabetic kidney disease [11], and diabetic depression [12]. Likewise, T2DM patients were more likely to have elevated SII in our subgroup analysis compared with those who did not have T2DM, Indicating that in ammation may be signi cantly involved in developing T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in ammatory markers, like SII, can also be used in the treatment of complications of T2DM. Guo et al found that T2DM patients had an increased SII in association with diabetic kidney disease [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that the ratios of different blood cell components are new in ammatory and immunoreactive markers, such as neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR), platelet-lymphocytes ratio (PLR), and systemic immune-in ammation index (SII, calculated by platelet count × neutrophil count/lymphocyte count), which have good predictive value in the outcome of cancer, chronic kidney disease, cardiovascular disease, rheumatic disease, type 2 diabetes, metabolic syndrome, and so on [10][11][12][13][14][15][16][17] . To our knowledge, limited studies have focused on evaluating the involvement of these markers in PMN, as well as their predictive value for treatment and progression in PMN.…”
Section: Introductionmentioning
confidence: 99%